HUBUNGAN SELF ESTEEM DENGAN INTENSI PENGGUNAAN MEDIA SOSIAL INSTAGRAM PADA MAHASISWA DI KOTA MEDAN - Lusiana Theresia br. Tohang; Ervina Marimbun R. Siahaan (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT This study demonstrates that self-esteem is one of the psychological factors associated with the intention to use Instagram among university students in Medan City. The negative relationship identified indicates that students with higher levels of self-esteem tend to exhibit lower intentions to use Instagram. These findings suggest that positive self-evaluation serves as a psychological resource that enables students to engage with social media more adaptively and reduces their reliance on social validation as the primary basis for shaping their behavior. Therefore, this study contributes to the fields of social psychology and digital psychology by providing empirical evidence that individual psychological characteristics play an important role in the formation of social media use intentions before actual usage behavior occurs. From a practical perspective, these findings highlight the importance of strengthening students' self-esteem through counseling services, personal development programs, and digital literacy initiatives within higher education institutions to promote healthier and more responsible social media use. Given that the observed correlation was relatively weak, self-esteem should not be considered the sole determinant of Instagram use intention. Future research is therefore encouraged to investigate additional psychological and social factors that may influence the intention to use social media, such as Fear of Missing Out (FoMO), social comparison, and self-control. Furthermore, future studies should involve more diverse participants from different regions or employ longitudinal research designs to provide a more comprehensive understanding of the dynamics underlying the relationships among these variables over time. ABSTRAK Interaksi mahasiswa dengan Instagram pada fase emerging adulthood tidak hanya dipengaruhi oleh perkembangan teknologi, tetapi juga oleh cara individu memandang dan menghargai dirinya sendiri. Evaluasi diri yang terbentuk selama proses perkembangan diduga berkontribusi terhadap munculnya intensi menggunakan media sosial sebagai bagian dari aktivitas sehari-hari. Penelitian ini mengeksplorasi hubungan antara self-esteem dan intensi penggunaan Instagram pada mahasiswa di Kota Medan melalui pendekatan kuantitatif dengan desain korelasional. Sebanyak 352 mahasiswa aktif berusia 18–24 tahun dari berbagai perguruan tinggi negeri dan swasta dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan Skala Self-Esteem yang diadaptasi dari Rosenberg Self-Esteem Scale (RSES) serta Skala Intensi Penggunaan Media Sosial yang dikembangkan berdasarkan Theory of Planned Behavior. Data dianalisis menggunakan statistik deskriptif, uji asumsi, dan uji korelasi dengan bantuan IBM SPSS Statistics. Hasil analisis menunjukkan bahwa sebagian besar responden memiliki self-esteem pada kategori tinggi, sedangkan intensi penggunaan Instagram berada pada kategori sedang. Uji korelasi menghasilkan hubungan negatif yang signifikan antara self-esteem dan intensi penggunaan Instagram (r = −0,128; p = 0,017), yang mengindikasikan bahwa peningkatan self-esteem diikuti oleh kecenderungan menurunnya intensi menggunakan Instagram. Temuan ini memperluas pemahaman mengenai peran self-esteem sebagai salah satu faktor psikologis yang berkaitan dengan pembentukan intensi penggunaan media sosial pada mahasiswa sebelum perilaku penggunaan benar-benar terjadi.